Improving Students and Community Participation in Preserving Mangrove Forest Bangkala Jeneponto South Sulawesi with a Constructivism based Booklet - Astuti Muh. Amin (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2018)
Knowledge dominantly affects community attitudes and participation in mangrove forest conservation. One of the effective ways to solve issues related to preserving mangrove forest in Jeneponto regency is to distribute a constructivism based booklet which introduces the functions, impacts, and management of the forest. This study was conducted in Bangkala District, Jeneponto regency, South Sulawesi from 11 August 2016 to 25 December 2016. Purposive sampling was employed to determine the research sample based on certain consideration. Data was collected using: (1) a questionnaire to elicit responses from some students and community members in Bangkala Jeneponto South Sulawesi towards a booklet developed on the constructivist theory; (2) another questionnaire and interview schedule to obtain community perception on the forest conservation activities; (3) socialization activities at schools and community centers related to the importance of sustainable mangrove forest development. Research findings indicate that: (1) the students and the community members of Bangkala, Jeneponto, South Sulawesi have provided positive and supportive responses towards the development of the constructivism booklet; (2) the society members have realized the significance of mangrove forest development; (3) overall, the students and the community members in Bangkala, Jeneponto, South Sulawesi have been highly involved in preserving the mangrove forest. Assistance to sustain this participation; however, is still necessary. Keywords: Booklet, Mangrove Conservation, Students, Participation, Community.